Recent Progress in the Development of Anticancer Agents - Eckhardt, S. (Current Medicinal Chemistry - Anti-Cancer Agents, 2002)
Cancer chemotherapy started with the discovery of the cytostatic effect of N-mustard and its derivatives more than five decades ago. This observation opened the way for the synthesis of various alkylating agents, antimetabolites and antimitotics expliciting antitumour activity against several human malignancies. The considerable toxicity of these drugs however, limited their application and only hormone-active products were relatively well tolerated. Besides, the majority of human malignant tumours proved to be chemoresistant. Consequently, there was still an urgent need for finding less toxic compounds possessing broader antitumour spectrum.Therefore, it became obvious that better understanding of the cellular metabolism - due to revolution in molecular biology - yielded new targets for cancer chemotherapeutic agents. Key enzymes active in signal transduction pathways could be blocked by new substances. Cell cycle control could be influenced by apoptosis inducers. Mitotic division could be inhibited by antitubulin agents. Multidrug resistance (MDR) could be modified by revertants.New concepts also emerged: a) chemoprevention, which is based on the principle, that since carcinogenesis is a genetically determined, progressive multistep process it can timely be reconverted into the direction of normal cellular metabolism by redifferentiating agents b) antimetastatic therapy: originally performed postoperatively as an adjuvant therapy nowadays before surgical intervention, in order to block vascular dissemination of tumor cells (neoadjuvant therapy) c) antiangiogenic therapy: substances capable to hinder the vessel production essential for the development of metastasis d) antitelomerase molecules inhibiting the immortal division capacity of DNA in malignant cells.All these new research approaches necessitate to review the existing drugs which are in clinical use or are investigational agents against human malignancies.
Keywords: procarbazine